Bridging the Skills Gap through Curriculum Reform: A Global Perspective - Hermansyah, Sam; Faradillah, Nurul (Eduscape : Journal of Education Insight, 2025)
The rapid changes in global economies, technologies, and societies highlight the urgent need for curriculum innovation. This review explores global best practices in curriculum reform, emphasizing adaptability, critical thinking, digital literacy, and interdisciplinary collaboration. Literature was collected from Scopus, Web of Science, and Google Scholar using structured keywords. The inclusion criteria focused on studies discussing curriculum design and future skills development in diverse contexts. Thematic synthesis revealed seven areas of innovation: flexible learning, project-based and industry-linked models, digital and AI-enhanced education, entrepreneurship, immersive pedagogies, communication skills, and transcultural collaboration. Results show that innovative models improve motivation, employability, and skill transfer. However, challenges remain, including limited resources, rigid policies, and ethical concerns in technology use. The discussion highlights the role of systemic factors such as policy, funding, and infrastructure. It also identifies best practices, including inclusive policymaking, cross-sector collaboration, and teacher professional development. Future research should prioritize longitudinal evaluations, standardized assessments of future skills, and interdisciplinary approaches. Overall, curriculum innovation emerges as a critical strategy for preparing learners to navigate uncertain professional landscapes and contribute to sustainable global development.